USING THINK PAIR SHARE TECHNIQUE WITH DESCRIPTIVE TEXT TO IMPROVE READING COMPREHENSION OF THE TENTH GRADERS OF SMA LTI IGM PALEMBANG - Sri Muryani; Jaya Nur Iman (Universitas Indo Global Mandiri, 2017)
The objectives of this research attempted to investigate whether or not using Think Pair Share (TPS) Technique gave significant improvement and significant difference on the tenth graders’ reading comprehension achievement of SMA LTI IGM. A quasi experimental design was used in this research. Two groups, experimental and control group, were assigned in this research in which each group consisted of 20 students, respectively. Intervention was given for 12 meetings including pretest and posttest administration. Reading comprehension test, in form of multiple choice question, was administered to measure the students’ reading comprehension. The research findings showed that (1) there was a significant improvement on the tenth graders’ reading comprehension achievement after being taught by using Think Pair Share Technique, and (2) there was a signifiant mean difference on the tenth graders’ reading comprehension achievement after being taught by using Think Pair Share Technique and those who were not. Therefore, the TPS technique significantly improved the tenth graders’ reading comprehension achievement of SMA LTI IGM.Key words : Think pair share technique, descriptive text, reading comprehension